The Emergence and Impact of Artificial Intelligence in Biotechnology - Ali, Jahanzaib (BIOEDUSCIENCE, 2024)
Introduction: Artificial intelligence (AI) has transformed many fields, including biotechnology. In recent years, artificial intelligence (AI) has played a critical role in altering research, drug development, genetic analysis, customized treatment, and other fields. The purpose of this review article is to investigate the numerous uses of AI in biotechnology, focusing on its impact on accelerating scientific advancement, improving data analysis, and driving innovation in the field. Method: Various AI approaches and methodologies used in biotechnology will be explored, including machine learning, deep learning, natural language processing, and picture identification. Results: This essay will also address important problems, future potential and ethical concerns regarding the use of AI in biotechnology. Conclusion: The integration of AI in biotechnology has redefined research paradigms, data analysis, and decision-making processes.